IMPLIKASI GEREJA TERHADAP RITUAL RAMBU SOLO’ PADA ORANG TORAJA DI KABUPATEN TANA TORAJA - Nia purwasih Sanggalangi; Erens E. Koodoh (KABANTI : Jurnal Kerabat Antropologi, 2023)
This research aims to know and describe the Church and Rambu Solo' Ritual in Toraja culture from the perspective of the church outside the Toraja Church towards the implementation of the ritual itself, especially among the Toraja people. This research uses Radcliffe-Brown's (1987) structuralism theory. The selection of informants in this study used purposive sampling technique, while the data collection techniques used in this study used observation and in-depth interviews. The results show the views of churches outside the Toraja Church towards the implementation of the rambu solo' ritual in Tana Toraja, where the Kibaid Church and the Pentecostal Church in Indonesia (GpdI) view the rambu solo' ritual as (1) a ritual that is not in line with God's word and violates church regulations, (2) a ritual that can cause debt burden, (3) does not describe the real atmosphere of grief. The existence of this view raises implications for the two churches themselves, namely in its application it can save costs, does not violate God's word, and does not require a lot of time.